Gadjah Mada stroke algorithm. Clinical strategy for distinguishing intracerebral haemorrhage from acute ischemic or infarction stroke - Rusdi Lamsudin Rusdi Lamsudin (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
A Gadjah Mada Stroke Algorithm (GMSA) as a clinical strategy to distinguish intracerebral haemorrhage from acute ischaemic or infarction stroke after the onset of stroke has been developed and validated (internal validity) in 229 stroke patients. An observational-prospective study design was conducted to validate GMSA (external validity) from 350 acute stroke patients in Dr. Sardjito Hospital, Yogyakarta from 1st December 1992 to 30th June 1996. The scope of the study are as follows: (1) validity of multiple-parallel test against CT-Scan to define intracerebral haemorrhagic stroke diagnosis, (2) significance of correlation between 8 group-variables of GMSA and intracerebral haemorrhagic stroke diagnosis, and (3) the validity of every group-variable to define intracerebral haemorrhagic stroke. This study showed that the GMSA as a clinical strategy have a high validity (external validity) to distinguish intracerebral haemorrhagic stroke from acute ischaemic or infarction stroke.Key words : Gadjah Mada stroke algorithm - diagnostic test - intracerebral haemorrhagic stroke -acute ischaemic stroke - infarction stroke